Pengaruh Profitabilitas, Likuiditas dan Leverage terhadap Penghindaran Pajak pada Industri Makanan dan Minuman - Franciscus Wongso; Wahyu Prasetya (Syntax Idea)
The purpose of this study is to analyze the effect exerted by Profitability, Liquidity and Leverage on Tax Avoidance in the Food and Beverage Sector Industry. Using descriptive quantitative method techniques, this study used a sample of twenty companies that had passed the criteria for sampling and used multiple linear regression analysis from SPSS 25 as a tool to calculate data. From the results of the analysis conducted, researchers get the results of the analysis as follows: (1) The Profitability (ROE) variable does not have a significant influence on the Tax Avoidance variable. (2) The Liquidity Variable (Current Ratio) does not have a significant influence on the Tax Avoidance variable. (3) The Leverage variable (DER) has a significant positive influence on the Tax Avoidance variable, so if the relationship between the Leverage variable and Tax Avoidance is inversely proportional when Leverage increases, it has an impact on decreasing the Tax Avoidance rate and vice versa.